Microbiota and Autoimmunity: exploring new avenues - Yurkovetskiy, Leonid (Cell Host Microbe, 2015)
Given the recognized role of the commensal microbiota in regulating host immunity to pathogens, it is not surprising that microbiota are also capable of regulating autoimmune responses. The underlying mechanisms of autoimmune regulation by the microbiota are just beginning to emerge. Here, we discuss possible pressure points towards the development of autoimmune diseases that can be influenced by the microbiota. Besides acting on the adaptive and innate arms of the immune response, the microbiota can affect the targets of autoimmunity directly, even during development in utero, and be involved in regulation of autoimmunity via interactions with hormones.